Fit gurl : the total-body turnaround program - Alcantara, Melissa (HarperOne, an imprint of HarperCollinsPublishers, 2020)
A no-nonsense fitness and nutrition plan by the Fitgurlmel Instagram star and Kim Kardashian's personal trainer outlines a four-step process for understanding one's body and its responses while committing to better health.